PENURUNAN CADMIUM DARI LIMBAH CAIR INDUSTRI PULP MENGGUNAKAN MEMBRAN KERAMIK BERBAHAN ADDITIVE DEDAK PADI - ., Sisnayati (Politeknik Negeri Sriwijaya, 2015)
The purpose of this research is to find an alternative pulp industrial waswater treatment system with filtration using ceramic membrane made from a mixture of natural clay, iron powder and rice bran as additive material in various composition. The experimental rig is equipped with silica and carbon active filter, ceramic membranes module, flowmeter, pressure gauge, and the circulation pump. The tested liquid waste is derived from one of the pulp industry in Sumatera Selatan. Process variables studied were operating time, filter composition and rice branparticle size. Parameters analyzed were TDS (Total Dissolved Solid), TSS (Total Suspensi Solid), pH, EC(Electrical Conductivity) and the concentration of Cadmium. Scanning Electron Microscope (SEM) analysis offilter surface and Brunnauer-Emmet Teller (BET) analysis for pores size determination were also performed. The results obtained showed that the application of ceramic membrane in composition of 87,5% of natural clay, 10% of material additive rice bran and 2,5% of iron powder can decrease cadmium concentration in pulp mill effluent up to 99,9%. Permeate flux was significantly decrease after 30 minutes. The SEM images and BET analysis of pore distribution showed that ceramic membrane has a random pore structure and can be classified as the microfiltration membrane.